Analysis of Self-Efficacy Anxiety on Academic Procrastination Behavior in Students - Intan Yudha Prastika; Silvia Mariah Handayani (International Journal of Educational Practice and Policy, 2025)
Academic procrastination is a problem that many students experience and has an impact on declining learning quality, increased stress, and low academic achievement. One of the internal factors that is strongly suspected to influence this behavior is self-efficacy anxiety, which is a condition when students doubt their ability to complete assignments, thus encouraging procrastination behavior. This study aims to analyze the effect of self-efficacy anxiety on academic procrastination behavior in students. The research method uses a quantitative approach with a survey design of 34 students selected through purposive sampling techniques. Data were collected using two Likert scales, namely the Anxiety Scale for Self-Disability and the Academic Procrastination Scale, and then analyzed through normality, correlation, and regression tests. The results showed that the data were normally distributed and there was a strong relationship between the two variables (R = 0.746). In addition, a significance value of 0.000 and a calculated t value greater than the t table showed that self-efficacy anxiety had a significant effect on academic procrastination behavior. This means that the higher the student's anxiety about their abilities, the higher their tendency to postpone academic assignments. This study concludes that anxiety about self-incompetence is an important psychological factor that needs to be considered in efforts to develop intervention programs to reduce academic procrastination in students.